TINJAUAN YURIDIS TERHADAP PENGGUNAAN KATA “MISS UNIVERSE” SEBAGAI MEREK YANG TERDAFTAR: Juridical Review of the Use of the Term "MISS UNIVERSE" as a Registered Trademark - Ramzy Sultan Nur Syarief; Simona Bustani (Reformasi Hukum Trisakti, 2025)
Brand gains more recognition and builds a good reputation in the market, its associated goods or services are more likely to sell well, making the brand a valuable asset for the company. However, a brand becoming famous does not mean it is free from disputes; it also provides individuals or companies the opportunity to gain benefits by leveraging the brand's popularity to boost their own business rapidly. The name MISS UNIVERSE is registered as trademark in the Intellectual Property Database. MISS UNIVERSE is well-known brand that has the potential to become generic, which could prevent others from using a trademark containing the same common words. The issues addressed in this thesis are does the term “MISS UNIVERSE” fall into category of common words?And what is the legal protection regarding the use of common words in the “MISS UNIVERSE” trademark? This research adopts normative approach with descriptive nature, utilizing primary  secondary data. Data collection is conducted through literature studies, while data analysis qualitative, and conclusions are drawn using deductive method. The result and conclution that MISS UNIVERSE trademark consists of common, generic words that should not be granted exclusive rights, as doing so could lead to unhealthy competition in the market.